Interleukin‐23 receptor defines T helper 1‐like regulatory T cells in oral squamous cell carcinoma - Wei Li; Ning An; Mingwei Wang; Xiguo Liu; Zhidan Mei (Immunity, Inflammation and Disease, 2022)
Abstract Background The immune responses play significant roles in the onset, progression, and outcome of oral squamous cell carcinoma (OSCC). CD4+ regulatory T cells (Tregs) significantly impact tumor immunity. However, their role in OSCC development remains elusive. Methods In a carcinogen‐induced mouse OSCC model, interleukin‐23 receptor (IL‐23R) expression on Tregs and Treg function were determined by flow cytometry. IL‐23R overexpression in Tregs was achieved by lentiviral infection, followed by evaluation of the expression of Forkhead box P3 (Foxp3), T‐bet, retineic‐acid‐receptor‐related orphan nuclear receptor gamma t, and cytokines by flow cytometry. Adoptive transfer assays were applied to analyze the function of IL‐23R−overexpressing Tregs in vivo. The cellular sources of IL‐23 were also determined by flow cytometry. Results IL‐23R− Tregs and IL‐23R+ Tregs were found in the tongues but not spleens of OSCC‐bearing mice. IL‐23R+ Tregs expressed lower Foxp3 but higher T‐bet than IL‐23R− Tregs. IL‐23R− Tregs produced abundant IL‐10 and transforming growth factor (TGF)‐β, while IL‐23R+ Tregs produced lower IL‐10 and TGF‐β but remarkably higher interferon (IFN)‐γ. Furthermore, IL‐23R+ Tregs possessed more phosphorylated signal transducer and activator of transcription (STAT3) and STAT4 than IL‐23R− Tregs. IL‐23R+ Tregs were less immunosuppressive than IL‐23R− Tregs, as evidenced by weaker inhibition of activated conventional T cells. IL‐23R overexpression in splenic Tregs remarkably reduced the expression of IL‐10 and TGF‐β but increased IFN‐γ expression when Tregs were adoptively transferred into OSCC‐bearing mice. In the OSCC microenvironment, macrophages, dendritic cells, and malignant OSCC cells produced IL‐23 which might modulate the function of IL‐23R+ Tregs. Conclusions This study unveils Treg heterogeneity, thus deepening the understanding of Treg biology and tumor immunity in OSCC.